Promotion Mix Tools Relevance for Marketing in Ethiopia: Literature Appraisal - Shashi Kant; Adugna Asefa Elema (RADINKA JAYA UTAMA PUBLISHER, 2023)
Promotion Mix is a concept of marketing communications planning that recognizes the added value of a comprehensive plan that evaluates the strategic roles of a variety of communication disciplines and combines these disciplines to provide clarity, consistency, and maximum communications impact. IMC can offer assistance in facilitating and delivering reliable messages over different channels of communication. The concept is particularly important in that it places incredible emphasis on the significance of the promotion mix. The objectives of the meta-analysis literature review are to examine IMC’s five tools for organizational performance: Advertising, Personal Selling, Sales Promotion, Direct Marketing and Public relation. Method design was based on secondary sources of information from various research publications and unpublished literature, magazines, Google Scholar, Science Direct, Research Gate, and books. The meta-analysis literature review The inclusion and exclusion of scanned literature was conducted with the help of PRISMA. For checking the effect size of the used literature, authors employed the Forest Plot based on partial correlation. The result of meta-analysis literature reviews is that IMC tools increase firm efficiency by increasing Overall profitability, overall brand performance, customer satisfaction, loyalty, new customers, sales volume, and Shareholder value of the organization’s services or products. The organizations manage the execution of Promotion Mix tools to significant performance.